Investigation of heat treatment on weld joint of steel and aluminum - Aida Syamsiah, Mohd Yusof (2012)
Dissimilar welding or Tailor Welded Blank (TWB) joint is defined as two or more sheets with equal or different materials, thickness, strength, or surface coatings are welded together. The objective of this project is to investigate the effect of heat treatment on the weld joints quality and determined the mechanical properties of the steel-aluminum weld joint. This project was performed to join aluminum alloy AA1100with stainless steel SUS 304in the thickness range of 3 mm in lap joint configuration. Among theprocess parameters varied were current flow, pre heating process. By metallurgy cross sections, hardness test and tensiletests, the effect of these process parameters on joint properties such as welding joint hardness, macrostructure defect and tensile strength could be elucidated. Based on theseresults, the penetration of the stainless steel with aluminum alloy will occur when the preheating process is applied. The optimum current without preheating is 85A and 95A for preheating process at 85ºC.